Analysis of inverse-piezoelectric-effect-induced lattice deformation in AlGaN/GaN high-electron-mobility transistors by time-resolved synchrotron radiation nanobeam X-ray diffraction. (2nd September 2021) - Shiomi, Haruna; Ueda, Akira; Tohei, Tetsuya; Imai, Yasuhiko; Hamachi, Takeaki; Sumitani, Kazushi; Kimura, Shigeru; Ando, Yuji; Hashizume, Tamotsu; Sakai, Akira
Abstract: We developed an in situ measurement system based on a synchrotron radiation nanobeam X-ray diffraction technique combined with a pump–probe method to investigate lattice deformation induced by the inverse piezoelectric effect in AlGaN/GaN high-electron-mobility transistor devices. Static and dynamic measurements using ultrafast X-ray pulses successfully captured changes in the c -plane lattice spacing in the AlGaN barrier layer coincided with the rising and falling edge of the gate voltage pulse at nanosecond resolution. This nanoscale time-resolved analysis reveals the influence of transient currents flowing in the device on the lattice deformation response during application of a gate voltage.